Effect Of Liquid Natural Rubber Addition To The Mechanical Properties Of Elastomeric Thermoplastic / Polyethylene Polyblend - Deswita Deswita; Sudirman Sudirman; Aloma Karo Karo; Dian Iramani (Balai Besar Kimia dan Kemasan, 2012)
Addition of liquid natural rubber (LNR) to elastomeric thermoplastic (ETP)/polyethylene (PE) polyblend has been done. The aim of this research is to study the effect of LNR addition to the ETP /PE polyblend using blending process. The blending process was done by mixing of ETP and PE with composition of 30% and 70% by weight respectively. LNR was added to the ETP /PE with composition of 3%, 5%, and 7% by weight, to form composite materials, refer as PLB-3, PLB-5 and PLB-7. The density of the specimen was measure by picno-meter, the mechanical properties were tested by Stograph R-1, the thermal property was analyzed by Differential Thermal Analysis (DTA) and the microstructure was observed by Scanning Electron Microscope (SEM). The result shows that the melting point of ETP/PE poly-blend increased from near 140oC to near 160oC with addition of LNR, but decomposition temperature decreased. Likewise, the mechanical properties of ETP/PE poly-blend exhibit the improvement after being added LNR. The mechanical properties show a rigid structure with the highest tensile strength of 191 Kg.m-2, and referred as the most optimum composition ETP/PE poly-blend. This condition is reached with addition of 5% by weight LNR showing regular and homogenous microstructure. It can be concluded that the addition of LNR could improve miscibility of ETP/PE, so that a better quality was obtained.